Protective Effects of Liposomal N-Acetylcysteine against Paraquat-Induced Cytotoxicity and Gene Expression - Panagiotis Mitsopoulos; Zacharias E. Suntres (Journal of Toxicology, 2011)
Paraquat (PQ) is a herbicide that preferentially accumulates in the lung and exerts its cytotoxicity via the generation of reactive oxygen species (ROS). There is no specific treatment for paraquat poisoning. Attempts have been made to increase the antioxidant status in the lung using antioxidants (e.g., superoxide dismutase, vitamin E, N-acetylcysteine) but the outcome from such treatments is limited. Encapsulation of antioxidants in liposomes improves their therapeutic potential against oxidant-induced lung damage because liposomes facilitate intracellular delivery and prolong the retention of entrapped agents inside the cell. In the present study, we compared the effectiveness of conventional N-acetylcysteine (NAC) and liposomal-NAC (L-NAC) against PQ-induced cytotoxicity and examined the mechanism(s) by which these antioxidant formulations conferred cytoprotection. The effects of NAC or L-NAC against PQ-induced cytotoxicity in A549 cells were assessed by measuring cellular PQ uptake, intracellular glutathione content, ROS levels, mitochondrial membrane potential, cellular gene expression, inflammatory cytokine release and cell viability. Pretreatment of cells with L-NAC was significantly more effective than pretreatment with the conventional drug in reducing PQ-induced cytotoxicity, as indicated by the biomarkers used in this study. Our results suggested that the delivery of NAC as a liposomal formulation improves its effectiveness in counteracting PQ-induced cytotoxicity.